Características químicas e perfil de ácidos graxos em gema de ovos de codornas (Coturnix coturnix japonica), alimentadas com ração suplementada com semente de linhaça - Silva, Walber Arantes da (2006)
The aim of this research was to improve the quality of quails' eggs as well as the need of obtaining an appropriate ratio n-6/n-3 in the composition of this food. 192 quails (Coturnix coturnix japonica) were used, in posture, of 58 weeks of age. The experiment had the duration of 84 days (4 cycles of 21 days). The birds were distributed and four treatments were carried out in function of different percentage of linseed (T1 = 0 (it controls); T2 = 1.5; T3 = 3 and T4 = 5%), used together with the normal ration. Differences (P>0.05), were not found, in the cholesterol levels during the four treatments and among the cycles. Considering the poliunsatured fatty acids linoleic (LA, 18:2n-6), linolenic (LNA, 18:3n-3), arachidonic (AA, 20:4n-6) and the docosahexaenóic (DHA, 22:6n-3) comprising 15.28, 15.66 17.3 16.54% of total fatty acids, in relation to T1, T2, T3 and T4 respectively. There was a increase (P<0,05) in the LNA, between control group and other treatments group. An increase (P<0,05) in the production of DHA was observed in response to the level of linseed incorporation in the diets. There was an increase (P<0,05) in the total poliunsatured fatty acids (AGPI) and a reduction (P<0,05) in the total of saturated fatty acid (AGS), resulting in a higher AGPI/AGS ratio. An increase (P<0,05) was also observed in the amount of AGPI n-3 between the control group and the other group treatments and as consequence, the ratio n-6/n-3 decreased from 21.30 (T1) to 4.52 (T4).